, , , , , . .

 

 

!

 

:

:

 

 

 

?

StudentHelp, , MS Word. , , antiplagiat.ru, etxt.ru advego.ru. StudentHelp , Word .


:


:

: . : 04.09.2012. : 2011. : 10. antiplagiat.ru: < 30%

():





() 19 . , , . . , . , , .. - .
- ( ) . , , .. . ().
, , , . . , , .














    .
    .
    .
.
, (2.1) , , (2.2) (2.4), : W1(p)
(2.5)
W2(p) z, ..
.(2.6)
, (2.1)
y=W1(p)x+W2(p)z.(2.7)
, (2.1). (2.3), (2.4) (2.7) .
(2.3) (2.4) , .
.
. () , - .
.
.

( 1 2 ),
,(2.8)
Y(s)=L{y(t)}, X(s)=L{x(t)}, Z(s)=L{z(t)}.
Z(s)=0, X(s)=0 , :
, .(2.9)
, =s. , s.
, (). , . . (2.1) , (2.9) .
(2.9), (2.8)
.(2.10)
, (2.8), (2.1) . , (2.8) (2.10) .
.

- . , .

    .

U(p) X1(p) X2(p) Xk-1(p) Y(p)


X1(p)=W1(p)U(p);. Y(p)=Wk(p)Xk-1(p).

, :


: (1)


    .


U(p)
. Y(p)



: (2)


    -
.
:
U(p) e(p) Y (p) Y(p) =W(p)e(p); Y(p) = W(p)Y(p);
e(p)=U(p) -Yoc(p) = U(p) -W(p) Y(p);
(-/+) (p), -
Yoc(p) : Y(p)=W(p)(U(p)-W(p)Y(p);

Y(p)(1 W(p)W(p))=W (p)U(p);

: (3)

, .


    .


U(p) U(p) Y(p)
. Yi(p)=W(p)U(p) ..



, , .


    .

U(p)

U(p) e(p) Y (p) Y(p)


Yoc(p)

W(p).



    .


U(p) e(p) Y(p) U(p) Y(p)


Yoc(p)


W(p).




.

, 0 0 .
f(p)
U(p) e(p) Y (p)

(-)
Yoc(p)


, , . , Y(p) e(p) :

Y(p)=W(p)U(p) + Wf (p)f(p); e(p)=We(p)U(p) + Wef (p)f(p); (4)

, e(t), f, Y(p).
:
    :
(5)
    .

(6)


We(p) - e(t) .
    ( ).

(7)


.
    ( ).

(8)

    .

(9)









.


. .



1. 1(t).







:


2. t(t).







:

: .. 1,:

; ;

: Y(p) = W(p) (pU(p)) = p W(p) U(p) , p W(p) U(p) . () :
() .
() , , . , : , , P(p) , , e-p .
3. ࠠ eat .


:

, , a.
, :

4. sin wt s wt.

:
sin wt = Im ejwt .. ejwt =cos wt + j cos wt.
cos wt = Re ejwt.
:
L{sin wt} = L(Im ejwt) = Im L(ejwt) = Im (1/(p-jw)) = Im((p+jw)/(p2+w2)) =
Im(p/(p2+w2 )+jw/ (p2+w2)) = w/ (p2+w2).
L{cos wt} = L(Re ejwt) = Re L(ejwt) = Re (1/(p-jw)) = Re((p+jw)/(p2+w2)) =
Re(p/(p2+w2 )+jw/ (p2+w2)) = p/ (p2+w2).


5. d(t)- ( , ).

d(t)- x(t):

(1)

d(t)- : L{d(t)} = 1.

: d(t)- - :

(2)


d/dt d/dt

...



, (), .

2:
H(t) W(p) .
    H(p)=W(p)/p. (3)

3:
h(t) ( ) W(p) d - .

    h(p)=W(p) 1=W(p). (4)

, h(p)=pH(p), (14).
, , :
. . Y(p)=W(p)U(p), d(t) , : Y(p)=W(p)1. 3: h(p) =W(p). :

(5)

, , 頠 h(t).
(5) (3) ():

: d*(t).
d*(t) d(t) (.. d(t) ), h*(t)h(t).
L{h*(t)} = W*(p) W(p).

: 1(t).


H(t) W(p):

: .

.


    "" , " " , , .
    - , .
    , , , , .
, , . , .. 1891.:
    .
    .
, .
():
, :
    .
, -.
, Ӡ :
..................



90% antiplagiat.ru, etxt.ru advego.ru




* . , .